Effect of calcium additive on product yields in hydrogasification of nickel-loaded Chinese sub-bituminous coal. (1st May 2015) - Yuan, Shenfu; Qu, Xuan; Zhang, Rong; Bi, Jicheng
Highlights: Ni–Ca catalyst reduces the reaction temperature and hydrogen pressure. Reactivity order: 1 wt% Ca > 0.5 wt% Ca > 1.5 wt% Ca > 2.0 wt% Ca > 0 wt% Ca. Ca makes Ni disperse on coal well, retards Ni sintering and poisoning. Ni–Ca catalyst causes the tar molecules to be hydrogenated before hydrocracking. Abstract: Hydrogasification of Chinese sub-bituminous coal was performed in a fixed-bed reactor to study the effects of Ni and Ni + Ca dual catalysts on the yields of light hydrocarbon liquids (HCL) and gaseous products (GPs). In the presence of calcium, a high yield of HCL and GPs was obtained. The main components in tar were light aromatic hydrocarbons (LAHs) such as BTX and naphthalene. The product yields strongly depended on the amount of co-loaded calcium. The maximum yields of LAHs and GPs were achieved to be 2.15 wt% (0.85 wt% of BTX and 0.7 wt% of naphthalene) and 51.51 wt% (CH4, CO, CO2 and C2 –C3 ), respectively, when using 5% Ni + 1% Ca dual catalysts at 750 °C and 1.0 MPa. The addition of Ca promoted the conversion of oxygen-containing species and aromatics to H2 O, CO, CO2, CH4 and BTX.